The Incidence of Surgical Site Infection and the Implementation of Prophylactic Antibiotic Use in General Surgery Patients - Ricky Wibowo (LifeSciFi, 2026)
Surgical Site Infection (SSI) occurs within 30 days after surgery or 90 days with an implant. Prophylactic antibiotics prevent SSI by reducing bacterial contamination, but misuse can increase infection risk and antibiotic resistance. This study aims to assess the incidence of SSI, types of surgery (clean or clean-contaminated), indications, and appropriateness of prophylactic antibiotics, and adherence to clinical guidelines. A retrospective observational design was used, analyzing secondary data at the General Surgery Clinic from March to June 2025. Adult patients (≥18 years) who received prophylactic antibiotics were included. Findings showed most patients were male, aged 18–25 and 46–55 years. Cefazolin was the most commonly used antibiotic (82.76%), followed by ceftriaxone (17.24%), primarily administered intravenously within 30 minutes before incision. Prophylactic antibiotic use was appropriate in 82.76% of cases, though timing adherence was low (35.63%). SSI incidence was 2.3%, occurring in both clean and clean-contaminated surgeries, with cases linked to ceftriaxone misuse. The study highlights the importance of stricter adherence to prophylactic antibiotic protocols, particularly regarding timing, to further reduce SSI risk.